Distinguishing feature of gut microbiota in Tibetan highland coronary artery disease patients and its link with diet - Yulan Ma (Nature Portfolio, 2021)
Abstract The prevalence of coronary artery disease (CAD) in Tibetan Highlanders is lower than that in plain-living individuals, but the mechanism still unclear. Gut microbiota (GM) disorder is considered one of the potential factors involved in the pathogenesis of CAD, but the GM characteristics of Tibetan Highlanders suffering from CAD are unknown. We sequenced the V3-V4 region of the 16S ribosomal RNA of gut bacteria from fecal samples from Tibetan and Han CAD patients and healthy individuals inhabiting the Qinghai-Tibet Plateau, as well as from Han CAD patients and healthy individuals living at sea level, and we analyzed the GM characteristics of these subjects by bioinformatics analysis. The results showed that Tibetan Highlanders suffering from CAD had higher GM α-diversity, with differently distributed cluster compared with healthy Tibetan Highlanders and Han CAD patients living at high and low altitudes. Genera Catenibacterium, Clostridium_sensu_stricto, Holdemanella, and Ruminococcus 2 were enriched in Tibetan Highlanders suffering from CAD compared with healthy Tibetan Highlanders and Han CAD patients living at high- and low-altitudes. Prevotella was enriched in Tibetan Highlanders suffering from CAD compared with Han CAD patients living at high- and low-altitudes. Moreover, Catenibacterium was positively correlated with Prevotella. Additionally, Catenibacterium, Holdemanella, and Prevotella were positively correlated with fermented dairy product, carbohydrate and fiber intake by the subjects, while Clostridium_sensu_stricto was negatively correlated with protein intake by the subjects. In conclusion, our study indicated that Tibetan Highlanders suffering from CAD showed distinct GM, which was linked to their unique dietary characteristics and might associated with CAD.